1997
DOI: 10.1073/pnas.94.20.10624
|View full text |Cite
|
Sign up to set email alerts
|

B cell receptor-associated protein α4 displays rapamycin-sensitive binding directly to the catalytic subunit of protein phosphatase 2A

Abstract: Recently, TAP42 was isolated as a high copy suppressor of sit4 ؊ , a yeast phosphatase related to protein phosphatase 2A (PP2A). TAP42 is related to the murine ␣4 protein, which was discovered independently by its association with Ig-␣ in the B cell receptor complex. Herein we show that a glutathione S-transferase (GST)-␣4 fusion protein bound the catalytic subunit (C) of human PP2A from monomeric or multimeric preparations of PP2A in a ''pull-down'' assay. In an overlay assay, the GST-␣4 protein bound to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(205 citation statements)
references
References 28 publications
7
194
1
3
Order By: Relevance
“…Our observations coincide with a number of recent studies documenting PP-2A association with different kinases [12][13][14][15][16][17][18][19][20][21][22]. For example, studies by Heriche et al [12] indicate that casein kinase 2α associates with PP-2A and causes activation of PP-2A.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observations coincide with a number of recent studies documenting PP-2A association with different kinases [12][13][14][15][16][17][18][19][20][21][22]. For example, studies by Heriche et al [12] indicate that casein kinase 2α associates with PP-2A and causes activation of PP-2A.…”
Section: Discussionsupporting
confidence: 92%
“…For example, PP-2A has been shown to bind the β2-adrenergic receptor [11], casein kinase 2α [12], homeobox gene 11 [13], tau [14], translation termination eukaryotic release factor 1 [15], adenovirus e4orf4 protein [16], α4 protein [17], neurofilament proteins [18,19] and small t and middle t antigens encoded by DNA tumour viruses [20,21]. Recent studies by Westphal et al [22] identified a calmodulin IV (CaMIV)-PP-2A complex in which PP-2A dephosphorylates…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, a human ortholog of TAP42 has been identified, the B-cell receptor-binding protein alpha 4 (a4), that interacts with the catalytic subunit of PP2A (Murata et al, 1997). As the rapamycin sensitivity of this interaction is controversial, it is not clear whether the mTOR pathway regulates formation of a phosphatase/Tap42-like complex in mammals, as in yeast (Murata et al, 1997;Nanahoshi et al, 1998).…”
Section: Tor-dependent Regulation Of Phosphatases?mentioning
confidence: 99%
“…Mammalian cells express a protein (α4/mTap42) that has 23% amino acid sequence identity with yeast Tap42. The α4/ mTap42 protein interacts directly with the catalytic subunits of PP2A, PP4 and PP6 [12][13][14][15] and modulates their enzyme activity [16]. The α4/mTap42 protein has also been reported to interact with mammalian S6K [17].…”
Section: Introductionmentioning
confidence: 99%